Annual Plan 1972-73 Government of Manipur - Planning Commission (Planning Commission, 1972)
Manipur is a new slate in the north-eastern border of the country. It is situated between latitudes 23°5O'N and 25°4I 'N and longitudes 93°2'E to 94°47'E and has an area of 22,356 sq. kms. It is bounded on the north by the stale of Nagaland, on the south by the Lushai Hills, on the east by Upper Burma and on the west by the district of Cachar, Assam. Out of about 854.4 kms. which constitute the boundary line an approximate length of 532 kms. forms the international boundary line with Burma. the state is cup shaped, bordered on all sides by hills running into north-south parallel folds with altitudes varying from 850 metres to 300 metres above sea level. These hills cover over nine-tenths of its total area.
Government of Manipur